Unraveling Epigenetic Changes in A. thaliana Calli: Impact of HDAC Inhibitors - Pírek, Pavlína; Kryštofová, Karolína; Kováčová, Ingrid; Kromerová, Anna; Zachová, Dagmar; Helia, Ondřej; Panzarová, Klára; Fajkus, Jiří; Zdráhal, Zbyněk; Lochmanová, Gabriela; Fojtová, Miloslava (Plants (Basel, Switzerland), 2023)
The ability for plant regeneration from dedifferentiated cells opens up the possibility for molecular bioengineering to produce crops with desirable traits. Developmental and environmental signals that control cell totipotency are regulated by gene expression via dynamic chromatin remodeling. Using a mass spectrometry-based approach, we investigated epigenetic changes to the histone proteins during callus formation from roots and shoots of Arabidopsis thaliana seedlings. Increased levels of the histone H3.3 variant were found to be the major and most prominent feature of 20-day calli, associated with chromatin relaxation. The methylation status in root- and shoot-derived calli reached the same level during long-term propagation, whereas differences in acetylation levels provided a long-lasting imprint of root and shoot origin. On the other hand, epigenetic signs of origin completely disappeared during 20 days of calli propagation in the presence of histone deacetylase inhibitors (HDACi), sodium butyrate, and trichostatin A. Each HDACi affected the state of post-translational histone modifications in a specific manner; NaB-treated calli were epigenetically more similar to root-derived calli, and TSA-treated calli resembled shoot-derived calli.
Keywords: histone posttranslational modifications; sodium butyrate; mass spectrometry; Arabidopsis thaliana; trichostatin A; callus formation; epigenetics